A Glimpse into Reading Preferences: A Case Study of Junior High School Students and Teachers - Irawan, Nanda Dwi; Safriyani, Rizka (Lingual Journal of Language and Culture, 2025)
This qualitative case study examines the reading habits and preferences of students at Muhammadiyah 13 Junior High School in Surabaya, East Java. Data were gathered using semi-structured interviews with two students and one English instructor to obtain insights into students' preferred reading materials, learning challenges, and effective learning practices. The research revealed that students exhibit a greater interest in reading captivating novels that have sympathetic characters and tackle contemporary societal concerns, as such texts facilitate personal connections with the material. Participants were queried about their favored reading subjects during the interview. The result indicated an interest in leisure and lifestyle, education, profession, and fashion. The teacher indicated tastes for fashion, art, and history. These replies underscore the range of themes that resonate with both students and teachers, emphasizing the necessity of providing broad reading materials to cater to varying interests. Students have considerable obstacles in cultivating robust reading habits, chiefly attributable to inadequate literacy abilities and insufficient motivation. These problems are frequently associated with uninspired and repetitive pedagogical approaches. To augment reading engagement, both the student and teacher highlighted the necessity for interactive learning tactics, including hands-on activities and group projects, which promote cooperation, involvement, and enhanced comprehension.